Efektivitas Layanan Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Komunikasi Interpersonal - Kanti, Wahyu Nila; Sugiyo, Sugiyo (Universitas Negeri Semarang, 2014)
The purpose of this research to obtain empirical data of the effectiveness of group guidance service with role playing technique to improve interpersonal communication. The population in this research is all of XI IPS 4 SMA N 14 Semarang which consist of 36 students and the samples were 10 students which taken using purposive sampling. Data collection methods were using psychological scale and observation. The data analysis techniques was using wilcoxon match pairs test. The research results showed that interpersonal communication before treatment included in moderate category and after treatment interpersonal communication included in high category. Wilcoxon match pairs test results showed that T (0) and T_table 5% (8) so that T_value<T_table (0 <8) which meant H_a was accepted and H_0 was rejected. It indicated that group guidance service with role playing technique effective in increasing interpersonal communication.